Immune Receptors Methods and Protocols - Rast, Jonathan P.; Booth, James W.D (Methods in Molecular Biology, Methods and Protocols, 2011)
Immunology has made significant progress in the past decade, driven forward by rapidly advancing technology and a renewed interest in the vast realm of innate immunity. The receptors that mediate these functions are at the front lines of both protective and regulative roles of the immune system.  In Immune Receptors: Methods and Protocols, expert researchers present a variety of experimental approaches to the characterization of immune receptors and the cell biology that mediates their functions.  These include imaging techniques that aim to understand receptor localization and trafficking, techniques to measure receptor-ligand interactions, strategies to identify novel ligands and methods to analyze downstream receptor signaling, as well as strategies for genomic and proteomic characterization of receptor repertoires. Written in the highly successful Methods in Molecular Biology™ series format, chapters include introductions to their respective subjects, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and tips on troubleshooting and avoiding known pitfalls.   Authoritative and practical, Immune Receptors: Methods and Protocols offers technical descriptions and protocols that will be useful both to investigators who are interested in carrying out these procedures and to those who seek a deeper understanding of the bench science that lies behind the immunology literature